Immune response and treatment targets of chronic hepatitis B virus infection: innate and adaptive immunity - Zheng, Peiyu; Dou, Yongqing; Wang, Qinying (Frontiers in Cellular and Infection Microbiology, 2023)
Chronic hepatitis B virus (HBV) infection is a major global public health risk that threatens human life and health, although the number of vaccinated people has increased. The clinical outcome of HBV infection depends on the complex interplay between viral replication and the host immune response. Innate immunity plays an important role in the early stages of the disease but retains no long-term immune memory. However, HBV evades detection by the host innate immune system through stealth. Therefore, adaptive immunity involving T and B cells is crucial for controlling and clearing HBV infections that lead to liver inflammation and damage. The persistence of HBV leads to immune tolerance owing to immune cell dysfunction, T cell exhaustion, and an increase in suppressor cells and cytokines. Although significant progress has been made in HBV treatment in recent years, the balance between immune tolerance, immune activation, inflammation, and fibrosis in chronic hepatitis B remains unknown, making a functional cure difficult to achieve. Therefore, this review focuses on the important cells involved in the innate and adaptive immunity of chronic hepatitis B that target the host immune system and identifies treatment strategies.